CXCL1 promotes tumor growth through VEGF pathway activation and is associated with inferior survival in gastric cancer. Issue 2 (10th April 2015) - Wei, Zhe-Wei; Xia, Guang-Kai; Wu, Ying; Chen, Wei; Xiang, Zhen; Schwarz, Roderich E.; Brekken, Rolf A.; Awasthi, Niranjan; He, Yu-Long; Zhang, Chang-Hua
Highlights The precise role and mechanism of CXCL1 on gastric tumor growth remain unclear. CXCL1 is overexpressed in gastric cancer (GC) and correlates with tumor stage and patient survival. CXCL1 enhances VEGF expression through the activation of JAK2-STAT3 signaling. CXCL1 promotes tumor growth and angiogenesis through the VEGF pathway. The CXCL1/CXCR2 pathway might be a promising therapeutic target in GC.